Unveiling GFAP Astrocytopathy: Insights from Case Studies and a Comprehensive Review of the Literature - Panagiotis Gklinos; Fotios Athanasopoulos; Vagia Giatrakou; Nikolaos-Achilleas Arkoudis; Dorothea Pournara; Eirini Giagkou; Argyro Tountopoulou; Sofia Vassilopoulou; Dimos-Dimitrios Mitsikostas (Antibodies)
Background: Autoimmune glial fibrillary acidic protein (GFAP) astrocytopathy, which was first identified in 2016, is an immune-mediated inflammatory disorder of the nervous system characterized by antibodies targeting GFAP. The exact pathogenic mechanisms, as well as the role of anti-GFAP antibodies, remain unclear; however, it seems that neuroinflammation is mediated by specific CD8+ T-cells and that neoplasms or viral infections can act as the initial trigger. Although the clinical spectrum of the disease is broad and heterogenous, GFAP astrocytopathy most commonly presents as meningoencephalitis with or without myelitis. Other symptoms include headache, visual disturbances, extrapyramidal or brainstem syndromes, and psychiatric manifestations including psychosis. The disease has a characteristically favorable response to steroid treatment while relapses occur in approximately 20–30% of the patients. Methods: We present two cases of GFAP astrocytopathy admitted to our hospital: a 43-year-old male with persistent headache and a 59-year-old female with acute dysarthria and swallowing difficulties followed by cognitive and behavioral symptoms. Results: Additionally, we conduct a comprehensive review of the literature to elucidate the role of anti-GFAP antibodies in disease pathogenesis and examine imaging characteristics, clinical manifestations, and treatment options for this recently described neuroimmunological condition. Conclusions: This review presents two unusual cases of GFAP-astrocytopathy and provides evidence for the pathogenesis, clinical presentation, imaging characteristics and treatment options of the disease.